Development of KUB Chicken in South Kalimantan - Suryana . (Indonesian Center for Animal Research and Development, 2017)
KUB chicken is a new breed of local chickens as the result of selection by the Indonesian Research Institute for Animal Production, Ciawi-Bogor. KUB chicken has been developed in South Kalimantan since early December 2013 at farmers assisted by livestock services in South Kalimantan and animal house belongs to the Assesment Institute of Agricultural Technology (AIAT) South Kalimantan. The purpose of this paper is to discuss the potency, production performance, and development opportunities of KUB chicken in South Kalimantan. KUB chickens have several advantages i.e. high egg production (160-180 eggs/hen/year), low brooding (±10%), faster growth, more savory meat taste, and adaptable to environment. Problems encountered in the development of KUB chicken in South Kalimantan are low hatchbility, expensive feed prices, and susceptible to diseases such as Newcastle Disease (ND) and Avian Influenza. Performance of KUB chicken at small farmers in South Kalimantan include egg production 65-67%, egg weight of 36.12-38.12 g/egg, feed consumption 85-105 g/head, feed conversion ratio 3.8-3.9, eggs fertility ranged between 90.21-92.61%, hatchability of eggs is 79.67-81.80% and DOC weight ranged from 34.50-36.86 g/head. Efforts to prevent diseases are the use of herb medicine, ND vaccination, and biosecurity. Appropriate feed technology, disease prevention and strengthen the marketing network are strategies that should be applied to develop KUB chicken in South Kalimantan. This will lead new job and increase farmers’ income.